Credit default swaps and corporate cash holdings - Marti G. Subrahmanyam; Dragon Yongjun Tang; Sarah Qian Wang (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We examine the effects of credit default swaps (CDS), a major type of over-thecounter derivative, on the corporate liquidity management of the reference firms. CDS help firms to access the credit market since the lenders can hedge their credit risk more easily using these contracts. However, CDS-protected creditors can be tougher in debt renegotiations and less willing to support distressed borrowers, causing some firms to become more cautious. Consequently, we find that firms hold significantly more cash after the inception of CDS trading on their debt. The increase in cash holdings by CDS firms is more pronounced for financially constrained firms and firms facing higher refinancing risk. Moreover, bank relationships and outstanding credit facilities intensify the CDS effect on cash holding. Finally, firms with greater financial expertise hold more cash when their debt is referenced by CDS. These findings suggest that CDS, which are primarily a risk management tool for lenders, induce firms to adopt more conservative liquidity policies.
Keywords: 330